Cloning and characterization of peroxidases associated with generalized defense reactions of plants against bacterial pathogens - Bozsó, Zoltán (Acta Biologica Szegediensis, 2002)
After bacterial infection pathogens can induce different types of plant defense responses. Recently we have investigated an early type of local induced resistance (EIR). EIR is induced by both pathogenic and non-pathogenic bacteria, and is not accompanied by plant cell death (HR), but can inhibit bacterial pathogens. We have found that plant peroxidase isoenzymes were activated some hours after bacterial inoculation in tobacco. A peroxidase gene, which activated during EIR was cloned. It was proved to be a peroxidase tpoxNI, which had previously cloned from tobacco mosaic virus (TMV) infected tobacco leaves. The transcription of tpoxNI gene was induced both by incompatible and saprophytic and was blocked by compatible Pseudomonas spp. and was slightly induced by water infiltration. The appearance of peroxidase proteins and its transcription activation may be a useful marker for detaile d Study of EIR.